HOW CAN ASIAN COUNTRIES DEAL WITH MEDICAL LIABILITY AND PATIENT COMPENSATION - Raposo, Vera Lúcia (PEOPLE: International Journal of Social Sciences, 2015)
All around the world countries are trying to find a solution to deal with medical liability and patient compensation. Some legal orders have opted for a no-fault system, in which the patient is compensated once certain requisites are fulfilled, which are apparently less demanding than the ones required for granting compensation in light of tort liability. However, many of the advantages of the no-fault model are actually illusory. In addition, this model is not suitable for most legal orders and certainly not for Asian countries, as the present paper intends to demonstrate. Conversely, we sustain the maintenance of the traditional model based on negligence (from the doctor or from the institution), but modified and complemented by some notes typical of the no-fault system and by the so-called alternative dispute resolution mechanisms.